Screening for Alternaria brassicicola resistance in the Brassicaceae: Bio-assay optimization and confocal microscopy insights into the infection process - Nowakowska,Marzena; Wrzesińska,Małgorzata; Kamiński,Piotr; Nowicki,Marcin; Lichocka,Małgorzata; Tartanus,Michał; Kozik,Elżbieta U (PeerJ PrePrints, 2016)
Heavy losses incited yearly by Alternaria brassicicola on the vegetable Brassicaceae – have prompted our search for sources of genetic resistance against the pathogen and the resultant disease, dark leaf spot. We optimized several parameters to test the performance of the plants under controlled conditions to this disease, including leaf age and position, inoculum concentration, and incubation temperature. Using these optimized conditions, we screened a collection of 38 Brassicaceae cultigens with two methods (detached leaf and seedlings). Our results show, that either method can be used for the A. brassicicola resistance breeding, while the plant’s genotype was crucial in determining its response to the pathogen. The laboartory bio-assays for A. brassicicola resistance were run under more stringent conditions than the field tests, and resulted in identification of two interspecific hybrids that might be used in breeding programs. Confocal microscopy analyses of the leaf samples provided data into the pathogen mode of infection: Direct epidermal infection or stomatal attack were related to plants’ resistance against A. brassicicola among the cultigens tested. Further, the actin network of the host cells reorganized around the papillas deposited under the pathogen’s appressorium.
Keywords: dark leaf spot; Alternaria blight; cabbages; resistance testing; controlled conditions; field assays; histochemical dual stain; actin staining